Comparative effectiveness of pharmacological interventions on mortality and the average length of hospital stay of patients with COVID-19: a systematic review and meta-analysis of randomized controlled trials. Issue 4 (3rd April 2022) - Akbari, Abolfazl; Razmi, Mahya; Sedaghat, Alireza; Alavi Dana, Seyyed Mohammad Matin; Amiri, Mahdi; Halvani, Ali Mohammad; Yazdani, Soroush; Sahab-Negah, Sajad
ABSTRACT: Introduction: Up to now, numerous randomized controlled trials (RCTs) have examined various drugs as possible treatments for Coronavirus Disease 2019 (COVID-19), but the results were diverse and occasionally even inconsistent with each other. To this point, we performed a systematic review and meta-analysis to assess the comparative effectiveness of pharmacological agents in published RCTs. Areas covered: A literature search was performed using PubMed, SCOPUS, EMBASE, and Web of Science databases. RCTs evaluating mortality and the average length of hospital stay to standard of care (SOC)/placebo/control were included. RCTs mainly were classified into five categories of drugs, including anti-inflammatory, antiviral, antiparasitic, antibody and antibiotics. Meta-analysis was done on 5 drugs classes and sub-group meta-analysis was done on single drugs and moderate or severe stage of disease. Expert opinion: Mortality and the average length of hospital stay of COVID-19 patients were significantly reduced with anti-inflammatory drugs (odds ratio [OR]: 0.77, 95% confidence interval [CI]: 0.69 to 0.85, P<0.00001, and mean difference [MD]: −1.41, CI:-1.75 to −1.07, P<0.00001, respectively) compared to SOC/control/placebo. Furthermore, antiparasitic was associated with reduced length of hospital stay (MD: −0.65, CI: −1.26 to −0.03, P<0.05) in comparison to SOC/placebo/control. However, no effectiveness was found in other pharmacological interventions.